DIFFERENCE OF VITAMIN C CONTENT IN PICKLED MANGO FRUIT - Palupi, Sri (Jurnal Penelitian Saintek, 2015)
his research is a survey one which aims at knowing the content of vitamin C of salted mangoes and knowing existances or non-extances of the content of vitamin C of salted mangoes in Jogjakarta Special Region (DIY). Knowing existances or nonextances of the differences of the content of vitamin C of salted mangoes the supply of vitamin C will -be known so that the need of vitamin C for someone can be considered as references. The samples are salted mangoes sold at Mirota Kampus, Gardena and Ramai shop. These shops only sell them every sample was analyzed to find out its water and vitamin C contents using "titrasi yodium" with four time repetitions. These data then was analyzed statistically using two ways of variant analysis. The summary of this research shows that the content of vitamin C every lOO-grama salted mango driedfrom Mirota Kampus has 0,141 gram, Gardena has 0,094 gram. There significant differences of the content of vitamin C of the salted mangoes from the 3 shops. A Null hypothesis (Ho) accepts, p > 0,05. It is suggested that people buys the salted mangoes at Mirota Kampus shop because its vitamin C content is higher.